Bioimpedance analysis combined with sagittal abdominal diameter for abdominal subcutaneous fat measurement - Lai, Chung-Liang; Lu, Hsueh-Kuan; Huang, Ai-Chun; Chu, Lee-Ping; Chuang, Hsiang-Yuan; Hsieh, Kuen-Chang (Frontiers in Nutrition, 2022)
Abdominal subcutaneous fat (ASF) is an independent predictor of mortality. This prospective observational study aimed to establish a rapid, safe, and convenient estimation equation for subcutaneous fat area (SFA) using bioimpedance analysis (BIA) combined with anthropometric measurements of the sagittal abdominal diameter (SAD). A total of 520 adult subjects were recruited and were randomly divided into 2/3 (n = 346) and 1/3 (n = 174) to form a modeling group (MG) and a validation group (VG), respectively. Each subject's abdomen was scanned at lumbar vertebra levels L3-L4 using computed tomography to obtain target variables (ASFCT). Estimated variables for all subjects included bioimpedance index (h2/Z), anthropometric parameters height (h), weight (Weight), waist circumference (WC), hip circumference (HC), and sagittal abdominal diameter (SAD), along with age and sex (male =1, female =0). SFA estimation equation SFABIA+SAD was established for the MG using stepwise multiple regression analysis. Cross-validation was performed using VG to evaluate the performance of the SFABIA+SAD estimation equation. Stepwise multiple regression analysis was applied from the MG, including SFABIA+SAD = 1.09 SAD – 29.90 Sex + 4.71 Weight – 3.63 Z/h2 – 1.50 h (r = 0.92, SEE = 28.10 cm2, n = 342, p < 0.001). Mean differences in SFABIA+SAD relative to SFACT were -1.21 ± 21.53, 2.85 ± 27.16, and -0.98 ± 36.6 cm2 at different levels of obesity (general, overweight, obese), respectively. Application of BIA combined with SAD in anthropometric parameters achieves fast, accurate and convenient SAF measurement. Results of this study provide a simple, reliable, and practical measurement that can be widely used in epidemiological studies and in measuring individual ASF.